ChemInform Abstract: Organocatalytic Enantioselective α‐Hydroxymethylation of Aldehydes: Mechanistic Aspects and Optimization. Issue 34 (August 2015) - Boeckman, Robert K. Jr.; Biegasiewicz, Kyle F.; Tusch, Douglas J.; Miller, John R.
Abstract The reaction proceeds via the 1, 3‐dioxane‐4‐ol intermediates (III) that can be trapped by Pinnick oxidation as α‐hydroxymethylalkanoic acids or by Wittig reaction with (IX) as 2‐methyl‐4‐hydroxymethyl‐alk‐2‐enoic acid esters.